Pelatihan Rangkaian Listrik Dengan Menggunakan Software Electronic Workbench Di Sma Negeri 14 Medan - Hutagalung, Siti Nurhabibah; Panjaitan, Melda (Cattleya Darmaya Fortuna, 2024)
In Physics subjects, so far students have studied, among other things, electronic circuits and an introduction to electronic components without any visual simulations using special electronics media or software. The minimal availability of supporting learning media hinders the creation of effective learning activities. To overcome the lack of availability of laboratory equipment at SMA NEGERI 14 MEDAN, especially for dynamic electrical circuit experiments, software called Electronic Workbench 5.12 was used which was developed in the form of a simulation. With the service activities carried out, it is hoped that students will be able to understand electronic design, be able to assemble simple electronic components using Electronic Workbench